Identification of Land Use on Riverbanks in the Mamasa Sub Watershed of the Saddang Watershed - Soma, Andang Suryana; wahyuni, wahyuni; Natalia, Christin (Jurnal Hutan dan Masyarakat, 2025)
The increasing population has led to a growing demand for non-agricultural land, resulting in land use conversion. Often, land needs extend to areas designated as protected, such as riverbanks, road margins, and spring borders. The riverbank boundary is defined as the outer limit of a river channel designated as the river protection boundary. In recent years, the Mamasa Sub-Watershed (Sub DAS Mamasa) has experienced forest conversion into plantations and agriculture, impacting the hydrological function of the area. On the other hand, there is a lack of data explaining the functions of riverbank areas in the Mamasa Sub-Watershed. The objectives of this research are (1) to understand the land use along the riverbanks in the Mamasa Sub-Watershed and (2) to identify the conformity of land use along the riverbanks in the Mamasa Sub-Watershed with the Regulation of the Republic of Indonesia No. 38 of 2011 concerning Rivers. The results of the land use identification along the riverbanks in the Mamasa Sub-Watershed include secondary forests (430.95 ha), primary forests (386.64 ha), mixed gardens (321.81 ha), rice fields (218.67 ha), fallow fields (179.25 ha), traditional vegetable gardens (194.65 ha), village settlements (51.83 ha), urban settlements (5.68 ha), coffee plantations (7.23 ha), cocoa plantations (17.93 ha), pine forests (59.60 ha), roads (23.51 ha), reservoirs (1.55 ha), shrublands (131.59 ha), bushes (28.94 ha), home gardens (18.88 ha), rock/sand expanses (3.73 ha), horticultural fields (9.86 ha), other open areas (2.37 ha), and an airport (0.41 ha). The appropriate land use along the riverbanks according to Regulation 38/2011 concerning Rivers is 1,043.01 ha (49.78%), while the non-compliant land use is 1,052.09 ha (50.22%).